Sociology a complete introduction - Oliver, Paul (Teach yourself books, 2015)
Sociology: A Complete Introduction is designed to give you everything you need to succeed, all in one place. It covers the key areas that students are expected to be confident in, outlining the basics in clear, jargon-free English and providing added-value features like summaries of key experiments and even lists of questions you might be asked in your seminar or exam. The text is split into four parts, with an emphasis throughout on understanding and treating all concepts with clarity and precision.